Application of nano and microformulations to improve the leishmanicidal response of quinoline compounds: a brief review - Romero, Angel H.; Gonzalez, Karina N.; Sabino, Marcos A. (Frontiers in Chemistry, 2025)
The quinolines represent an important scaffold for the development of leishmanicidal agents. In particular, the use of nano and microformulations has emerged as a powerful tool to improve the therapeutic profile of leishmanicidal drugs, favoring bioavailability, transportation to key targets, metabolic protection, and immunostimulating responses. This mini-review seeks to provide a general perspective about the use of nano/microencapsulation for the development of leishmanicidal formulations based on quinoline, giving an overview of the various cases of encapsulation, analyzing the repercussions of the type of polymeric matrix (synthetic or natural polymer), type of formulation (polymeric or metallic nanoparticles, micelles, liposomes, etc.), drug loading percentage, and release rate of quinoline drug.